ЛЕКСИЧЕСКИЕ ВАРИАНТЫ ТЮРКСКОЙ ЛЕКСИКИ (КАРАКАЛПАКИЗМОВ) - Каландарова, Г.Н. (SCIENCE and SOCIETY, 2020)
The article examines the importance of studying the Turkic vocabulary, which is of great scientific interest not only in philological terms, but also as a subject for ethnographic and historical research.
Keywords: lexicon; Turkisms; borrowing; bilingualism; lexical group; Türkic lexeme